Functional Diversity of Mitochondrial Peptidyl-tRNA Hydrolase ICT1 in Human Cells - Chicherin, I.V.; Dukhalin, S.V.; Khannanov, R.A.; Baleva, M.V.; Levitskii, S.A.; Patrushev, M.V.; Sergiev, P.V.; Kamenski, P. (Frontiers in Molecular Biosciences, 2021)
Mitochondria are energy producing organelles of the eukaryotic cell, involved in the synthesis of key metabolites, calcium homeostasis and apoptosis. Protein biosynthesis in these organelles is a relic of its endosymbiotic origin. While mitochondrial translational factors have homologues among prokaryotes, they possess a number of unique traits. Remarkably as many as four mammalian mitochondrial proteins possess a clear similarity with translation termination factors. The review focuses on the ICT1, which combines several functions. It is a non-canonical termination factor for protein biosynthesis, a rescue factor for stalled mitochondrial ribosomes, a structural protein and a regulator of proliferation, cell cycle, and apoptosis. Such a diversity of roles demonstrates the high functionality of mitochondrial translation associated proteins and their relationship with numerous processes occurring in a living cell.